(untitled) (Journal of Dhaka National Medical College & Hospital, 2020)
Background: Oral diseases are major public health problem owing to their high prevalence and incidence in all regions of the world. Current report says that 11.9 percent people are affected by oral cancer. Objective: Therefore this study has been undertaken to evaluate the histopathological spectrum of oral and oropharyngeal lesions. Methods: A prospective, descriptive cross-sectional study was conducted in the Department of Pathology, Dhaka Medical College (DMC).during a 24 months period from January 2016 to December, 2017. Patients of different age group and both sex were selected for this study according to inclusion and exclusion criteria. Results: Present study comprised of 203 cases oral and oropharyngeal lesions of which 94 (46%) were male, and 109 (54%) were female. The age range was from 3 to 86 years with an average of 47.3 years, the highest number of patients to be in 5th decade. According to site of involvement, buccal mucosa is the commonest site. Among 203 cases, 18 (9%) were non neoplastic inflammatory lesion, 39 cases (19%) were tumour like condition, 33 cases (16%) were benign tumour, 15 cases (8%) were potentially malignant condition and 98 cases (48%) were malignant tumour. Conclusion: This small study gives an understanding of the national scenario about histomorphological pattern of oral and oropharyngeal lesions. J. Dhaka National Med. Coll. Hos. 2020; 26 (01): 21-25